The effectiveness of botulinum toxin type A preparations in the consequences of gunshot wounds (clinical case) - T. I. Dutova; I. N. Banin; Yu. V. Lyutikov; N. A. Ermolenko; P. V. Yurov; E. A. Portnykh (Лечащий Врач)
Background. The events of the last two years of a Special Military Operation have obliged doctors of all specialties to re-evaluate the methods of diagnosis, treatment, and anesthesia of patients with the consequences of gunshot wounds. The article presents a clinical case of a severe pain syndrome (piriform muscle syndrome) due to a gunshot wound and its treatment using botulinum therapy. Botulinum toxin type A has a unique analgesic effect, which has expanded the scope of its application in clinical practice.Objective. The purpose of the study was to evaluate the effectiveness of botulinum toxin type A preparations in severe pain syndrome due to gunshot wounds.Results. As a result of the treatment with botulinum toxin type A, a pronounced positive dynamics of pain relief was obtained in case of piriform muscle syndrome, which developed as a result of the consequences of a gunshot wound.Conclusion. Piriform muscle syndrome is a disorder that often manifests as a clinical picture of different pathologies. A late diagnosis or inadequate therapy can lead to the pathological changes in the sciatic nerve. The key to the effectiveness of the method used is the early detection of such disorder. Currently, the range of preparations for the treatment of pain syndrome is quite wide, but only a methodologically proper injection can increase the effectiveness of piriform muscle syndrome treatment and reduce the risk of complications, which is impossible without the use of imaging techniques. Thus, we believe that injections into the area of the piriform muscle under the visualization control should become the method of choice in the treatment of pain of such localization.